Soulstice - Holt, Simon (Penguin Group Ltd, 2010)
Reggie Halloway thought she was finished with the Vours - the demons who had possessed her brother, Henry-forever. She had once faced them in a deathly battle for Henry's soul and now she wants to forget them. But Quinn, the Vour she left at the bottom of a lake, is back.
Keywords: Juvenile Literature-Scary